Understanding early and late identification of dyslexia: a narrative review of diagnostic timing, systemic barriers, and educational equity - Nik Zatul-Iffah N. Mohd Nabil; Mohd Effendi @ Ewan Mohd Matore; Mohd Syazwan Zainal (Penerbit Universiti Kebangsaan Malaysia, 2025)
Dyslexia is a common neurodevelopmental disorder that profoundly affects reading, writing, and spelling, often leading to persistent academic underachievement and emotional difficulties. Early identification plays a critical role in enabling effective intervention. However, many students remain undiagnosed or are diagnosed late, limiting access to timely support. This narrative literature review (NLR) synthesises current evidence on the timing of dyslexia diagnosis, specifically examining early diagnosed, late-diagnosed and late-emerging cases. By exploring how diagnostic timing influences educational trajectories and psychosocial outcomes, the review provides a nuanced understanding of the long-term implications for learners. It further examines the genetic, environmental and systemic factors that contribute to the risk of delayed or inaccurate identification, highlighting the complex interaction between biological predispositions and external influences such as teacher preparedness, culturally relevant assessment practices and equitable access to resources. Key findings underscore the importance of integrating technology-driven tools and ongoing professional development for educators to reduce disparities in early detection and intervention. These findings also align with the United Nations Sustainable Development Goals, particularly SDG 4.1 and 4.5 which emphasize equitable access to quality education and SDG 10.2, which advocates for social inclusion regardless of disability. Ultimately, this review calls for adaptive, contextually responsive policies that address systemic barriers and promote early, accurate identification of dyslexia. Such measures are essential not only for advancing educational equity but also for fostering broader goals of social justice and inclusion in diverse educational contexts.